2023
DOI: 10.3390/molecules28134919
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dye-Modified Metal–Organic Framework as a Bifunctional Fluorescent Probe for Visual Sensing for Styrene and Temperature

Abstract: A novel fluorescent probe (C460@Tb-MOFs) was designed and synthesized by encapsulating the fluorescent dye 7-diethylamino-4-methyl coumarin (C460) into a terbium-based metal–organic framework using a simple ultrasonic impregnation method. It is impressive that this dye-modified metal–organic framework can specifically detect styrene and temperature upon luminescence quenching. The sensing platform of this material exhibits great selectivity, fast response, and good cyclability toward styrene detection. It is w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The (RT.pH13)-based sensor displayed partial recovery after evacuating the gas chamber, while the (RT.pH13.C)-based sensor fully recovered the initial response signal at low C 8 H 8 concentrations. While (RT.pH13)-and (RT.pH13.C)-based sensors were evaluated at RT, the latest styrene sensors that can be potentially used for lung disease diagnosis required elevated temperatures within the range of 120-260 • C [96][97][98]. These high temperatures pose challenges for certain industrial applications and impede the development of flexible sensors on low-cost substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The (RT.pH13)-based sensor displayed partial recovery after evacuating the gas chamber, while the (RT.pH13.C)-based sensor fully recovered the initial response signal at low C 8 H 8 concentrations. While (RT.pH13)-and (RT.pH13.C)-based sensors were evaluated at RT, the latest styrene sensors that can be potentially used for lung disease diagnosis required elevated temperatures within the range of 120-260 • C [96][97][98]. These high temperatures pose challenges for certain industrial applications and impede the development of flexible sensors on low-cost substrates.…”
Section: Resultsmentioning
confidence: 99%
“…204 Based on the differences in guest molecules, the main types of LG-MOFs include organic dyes@MOF, metal ions@MOF, metal nanoclusters@MOF, quantum dots@MOF and perovskites@MOF. 204–207 Thus far, LMOF-based detection platforms have been developed to evaluate the living environment of plants (Fig. 32).…”
Section: Applications Of Fluorescent Nano-chemosensorsmentioning
confidence: 99%
“…Some specific lanthanide ions can provide narrow emission spectrum with large Stokes shifts through energy-transfer induced D→F transition, from which generates long-time delayed fluorescence with τ in the range of several to hundred μs [ 37 ]. Mostly, Eu 3+ and Tb 3+ [ 38 ] are the most inclined ions to provide such sensitized fluorescence. However, commonly Eu 3+ and Tb 3+ -based materials are usually unstable, easy to photo-bleach and possess narrow light-absorbing range and low photon efficiency.…”
Section: Cofs Fluorescence Sensing Materials For the Detection Of Ant...mentioning
confidence: 99%
“…Yu et al reported a Eu 3+ -modified bipyridine DPy-TFPB-COF [ 38 ], which acted as an efficient tetracycline ratiometric fluorescent sensor as illustrated in Fig. 1 .…”
Section: Cofs Fluorescence Sensing Materials For the Detection Of Ant...mentioning
confidence: 99%